1967
DOI: 10.1111/j.1744-7348.1967.tb05926.x
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments on sugar‐beet downy mildew (Peronospora farinosa)

Abstract: SUMMARY The numbers of sugar‐beet plants infected with downy mildew in experimental crops increased slowly over a period of 8–15 weeks from late May. Few new infections appeared after the middle of August, although less than half the plants were then infected. Most infected plants recovered, and recovery was most rapid and complete in young plants, irrespective of the weather. Plants infected when young produced small roots, but their sugar content and juice purity at harvest was similar to those of uninfected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The proportions of plants in each stock which showed severe symptoms of downy mildew were recorded on five dates (Table 4), but sporulators were not distinguished from non-sporulators. The results confirmed previous observations by Byford (19676) that most plants recover from infection with downy mildew, but suggested that plants of some sugar-beet stocks recovered more quickly from the disease than those of other stocks. Stocks that had been selected for resistance to P. farinosa were more resistant at each scoring date than the stocks from which they had been derived.…”
Section: Cambridge Experiments 1965supporting
confidence: 90%
“…The proportions of plants in each stock which showed severe symptoms of downy mildew were recorded on five dates (Table 4), but sporulators were not distinguished from non-sporulators. The results confirmed previous observations by Byford (19676) that most plants recover from infection with downy mildew, but suggested that plants of some sugar-beet stocks recovered more quickly from the disease than those of other stocks. Stocks that had been selected for resistance to P. farinosa were more resistant at each scoring date than the stocks from which they had been derived.…”
Section: Cambridge Experiments 1965supporting
confidence: 90%
“…Due to taxonomic confusion, downy mildew was previously classified as Peronospora farinosa and considered as such by most studies for about 50 years [ 24 , 25 , 26 ]. Byford (1967a,b) [ 27 , 28 ] investigated cross-inoculation experiments and concluded the division of three formae speciales (f. spp.)…”
Section: Downy Mildew Of Quinoamentioning
confidence: 99%
“…The disease is potentially important in most areas where the root crop is grown in the U.K. Disease development is complex and few comprehensive assessments of possible yield losses have been made. From studies of yield losses in individual roots, Byford (1967b) concluded that infection of 20 % of the plants of a moderately resistant variety in July and August could lead to 10 yo reduction of sugar yield. Disease incidence in root crops is usually greatest when they are grown near to seed crops of sugar beet or mangolds, in which the fungus readily overwinters (Byford & Hull, 1967).…”
Section: Introductionmentioning
confidence: 99%